(untitled) (Journal of Mathematics Mechanics and Computer Science, 2021)
The paper considers a six-link straight-line conversion scissor mechanism, which is used as a new design of the conversion mechanism of the beamless rod pump drive. The purpose of balancing the conversion mechanism of rod pump drive (RPD) is to reduce the required engine power and its uniform load per cycle of movement. The task of optimal dynamic balancing of the conversion mechanism of the RPD is to determine the optimal values of the weight of the counterweight GCW and the distance l = OL from the crank axis at which the minimum peak value of the balancing moment on the crank shaft is provided. In practice, the determination of these values is carried out empirically by comparing two peak values – the torque on the crank shaft for the cycle of the mechanism movement. The result kinetostatics analysis, solving the equilibrium equations of the six-link scissor mechanism, determined reactions of mechanism hinges and values – the torque on the shaft of the crank shaft per cycle of movement of the mechanism. Also, for the reliability of the results, according to the principle of possible movements through the power of the acting forces, values – the torque on the crank shaft were determined. Key words: Drive, transforming mechanism, crank, connecting rod, balancer, poise, analysis.